2010
DOI: 10.1186/1471-2407-10-516
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics and outcomes of patients with acute myelogenous leukemia admitted to intensive care: a case-control study

Abstract: BackgroundThere is limited epidemiologic data on patients with acute myelogenous (myeloid) leukemia (AML) requiring life-sustaining therapies in the intensive care unit (ICU). Our objectives were to describe the clinical characteristics and outcomes in critically ill AML patients.MethodsThis was a retrospective case-control study. Cases were defined as adult patients with a primary diagnosis of AML admitted to ICU at the University of Alberta Hospital between January 1st 2002 and June 30th 2008. Each case was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
38
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 32 publications
4
38
0
Order By: Relevance
“…Previous studies have demonstrated that when needed, continuation of the chemotherapeutic regimen after ICU admission could improve the outcome of these patients [29]. Our results extend this observation, and suggest that an active therapeutic strategy must be taken after ICU discharge.…”
Section: Discussionsupporting
confidence: 84%
“…Previous studies have demonstrated that when needed, continuation of the chemotherapeutic regimen after ICU admission could improve the outcome of these patients [29]. Our results extend this observation, and suggest that an active therapeutic strategy must be taken after ICU discharge.…”
Section: Discussionsupporting
confidence: 84%
“…113 In the ICU setting, few data are available for patients with hematological malignancies. 10,114,115 Studies are warranted to evaluate long-term outcome in allo-HSCT long-term ICU survivors. The place of patient and family wishes and implication in the shared decision-making process also needs to be clearly evaluated.…”
Section: Limitations Of the Published Experiences And Unresolved Issuesmentioning
confidence: 99%
“…The studies were purely prognostic single cohort studies, with the exception of two. Hill et al [49] and des Ordons et al [44] employed prognostic case-control cohort designs and compared outcomes of people with a hematological malignancy admitted to the ICU against medical controls. The studies with a single cohort included people with a hematological malignancy or in comparison studies, only data on the group with a hematological malignancy were extracted and included in the results of this review.…”
Section: Resultsmentioning
confidence: 99%
“…No study discussed patients’ socio-economic status or education level. Fourteen studies included all types of hematological malignancies [32, 33, 35, 36, 39, 42, 4649, 51, 53, 56, 57]; five sampled patients with acute leukemia [38, 40, 41, 44, 54]; eight looked at people who had undergone hematopoietic stem cell transplantation [30, 31, 34, 37, 43, 50, 52, 55]; and one was specifically focused on people with human immunodeficiency virus associated lymphoma [45]. The patient population was predominantly treated with aggressive curative or life-prolonging intent, as most studies ( n  = 24) had admission to the ICU as a criterion for inclusion.…”
Section: Resultsmentioning
confidence: 99%